Investigation on Acoustic Properties of Thruster Chamber with Coaxial Injectors and Plenum Chamber - Dekun Gao; Jianxiu Qin; Huiqiang Zhang (International Journal of Aerospace Engineering)
Based on the URANS equation, a numerical simulation is carried out for acoustic properties of the thruster chamber with coaxial injectors and plenum chamber in a liquid rocket engine. Pressure oscillations with multiacoustic modes are successfully excited in the chamber by using the constant volume bomb method. FFT analysis is applied to obtain the acoustic properties of eigenfrequencies, power amplitudes, and damping rates for each excited acoustic mode. Compared with the acoustic properties in the model chamber with and without an injector as well as with and without the plenum chamber, it can be found that the injector with one open end and one half-open end still can work as a quarter-wave resonator. The power amplitudes of the acoustic mode can be suppressed significantly when its eigenfrequency is close to the tuning frequency of the injector, which is achieved by Cutting down the pressure Peak and Raising up the pressure Trough (CPRT). Compared with the acoustic properties in the model chamber with and without the plenum chamber, it can be found that 1L acoustic pressure oscillation is inhibited completely by the plenum chamber and other acoustic pressure oscillations are also suppressed in a different extent. The injector and plenum chamber have a little effect on the eigenfrequencies and damping rate of each acoustic mode. For multimode pressure oscillation, it is better for tuning frequency of the injector closing to the lower eigenfrequency acoustic mode, which will be effective for suppression of these multiacoustic modes simultaneously.